Physicochemical characterization of natural and acetylated thermoplastic cassava starch (2011)
Thermoplastic starch (TPS) was obtained from natural and acetylated cassava starch using a twin screw extruder and then conditioned at 25 ºC and 54 % of relative humidity. It was found that the crystallinity index, calculated as the ratio of the IR peaks at 1047 (crystalline phase) and 1022 cm¯¹ (amorphous phase), decreases due to the effect of a plasticization process. Also, as expected, SEM micrographs show that the plasticization process destroyed the starch granular structure almost completely and an amorphous mass was obtained. The TGA results indicated that the activation energy, Ea, was also reduced by the plasticization process. The acetylated TPS shows a decrease in Tg, in tensile strength and in the percentage of moisture absorption compared to natural TPS but a larger strain at the breaking point. This behavior suggests that the chemical modification reduces the secondary interactions between starch chains due to the substitution of the hydroxyl groups by acetates.